Who spoke that language? Assessing early face-language associations in monolingual and bilingual infants - Marcet, Laia; Birulés, Joan; Bosch, Laura; Pons, Ferran (Frontiers in Psychology, 2024)
In bilingual communities, knowing the language each speaker uses may support language separation and, later, guide language use in a context-appropriate manner. Previous research has shown that infants begin to form primary associations between the face and the language used by a speaker around the age of 3 months. However, there is still a limited understanding of how robust these associations are and whether they are influenced by the linguistic background of the infant. To answer these questions, this study explores monolingual and bilingual infants' ability to form facelanguage associations throughout the first year of life. A group of 4-, 6-and 10-month-old Spanish and/or Catalan monolingual and bilingual infants were tested in an eye-tracking preferential-looking paradigm (N=156). After the infants were familiarized with videos of a Catalan and a Spanish speaker, they were tested in two types of test trials with different task demands. First, a Silent test trial assessed primary face-language associations by measuring infants' visual preference for the speakers based on the language they had previously used. Then, two Language test trials assessed more robust face-language associations by measuring infants' ability to match the face of each speaker with their corresponding language. When measuring primary face-language associations, both monolingual and bilingual infants exhibited language-based preferences according to their specific exposure to the languages. Interestingly, this preference varied with age, with a transition from an initial familiarity preference to a novelty preference in older infants. Four-month-old infants showed a preference for the speaker who used their native/dominant language, while 10-month-old infants preferred the speaker who used their non-native/non-dominant language. When measuring more robust face-language associations, infants did not demonstrate signs of consistently matching the faces of the speakers with the language they had previously used, regardless of age or linguistic background. Overall, the results indicate that while both monolingual and bilingual infants before the first year of life can form primary face-language associations, these associations remain fragile as infants seemed unable to maintain them when tested in a more demanding task.